Assessment of the coordinated relationship between blue-green space and urbanization in coastal mountain cities based on spatiotemporal evolution analysis: A case study in Qingdao, China - Chao Li; Siyan Yue; Xin Liu; Huan Dai; Xingyu Li (Ecological Indicators)
Urban blue-green space is under great threat due to the huge impact of rapid urbanization. As representatives of high-density urban agglomerations, coastal mountain cities, while possessing a complex blue-green system, are also subject to great ecological vulnerability. To support the sustainable growth of cities, it is crucial to investigate the synergistic relationship between urbanization and blue-green space in coastal mountainous regions. Taking Qingdao, a typical fast-developing coastal mountainous city, as an example, the study analyzed the spatiotemporal evolution characteristics of blue-green space and urbanization in the study area from 2000 to 2020 on a grid-scale and explored the spatiotemporal dynamic trend of the coupling coordination degree of urbanization and blue-green space based on the coupling coordination model. The results showed: (1) From 2000 to 2020, land use in Qingdao experienced drastic changes. The main change was the encroachment of urban into the blue-green spaces, which led to the fragmentation and complexity of the landscape pattern of blue-green space, with the most significant change in the central coastal area. (2) The development levels of green space and blue space generally showed a downward and then upward trend, and the level of urbanization continued to rise. The development level between blue-green space and urbanization mainly showed a negative spatial correlation. (3) The coupling degree between composite systems showed a steady upward trend in time, but still lacked highly coordinated regions. Spatially, the coupling degree between the systems had a strong difference and agglomeration, showing the general characteristic of “High in the center, low in the north and south, and decreasing inward from the coast”, which was more spatially consistent with the level of urbanization. This study is of great significance to urban sustainable development planning of coastal mountain cities.